2021
DOI: 10.3390/insects12080718
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs of Two Maize Lepidopteran Pests Fed on Bacillus thuringiensis (Bt) Diets Enriched with Vitamins A and C

Abstract: Serious malnutrition problems occur in developing countries where people’s diets are mainly based on staple crops. To alleviate this, high-production crops are being developed that are better adapted to climate change, enriched in micronutrients and vitamins, or resistant to pests. In some cases, new varieties have been developed with several of the characteristics mentioned above, such as biofortified and pest-resistant crops. The development of biofortified Bacillus thuringiensis (Bt) crops raises the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The results confirmed that feeding on a Bt toxin diet throughout the larval instar prolongs development, producing lighter pupae from the larvae that survive. These findings have also been observed in a previous work on the same species, with a similar procedure (larvae fed on lyophilized Bt diet) [ 8 ] and on other related species, such as H . zea [ 28 ] but with larvae from field conditions, fed on sublethal amounts of the toxin.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The results confirmed that feeding on a Bt toxin diet throughout the larval instar prolongs development, producing lighter pupae from the larvae that survive. These findings have also been observed in a previous work on the same species, with a similar procedure (larvae fed on lyophilized Bt diet) [ 8 ] and on other related species, such as H . zea [ 28 ] but with larvae from field conditions, fed on sublethal amounts of the toxin.…”
Section: Discussionsupporting
confidence: 87%
“…The pupae were maintained at 15°C and 16:8 LD photoperiod to synchronize adult emergence. When the number of females and males was considered sufficient to full a mating cage (6 females and 5 males per cage, [ 8 ]) the pupae were placed in the general rearing conditions in pots with daily moistened soil. Adults (F0) from these pupae were placed in the mating cages (cylindrical methacrylate tubes of 25 cm diameter and 40 cm height, closed at the base with an expanded polystyrene lid, and sealed at the top with white gauze) and given a drinker of honey solution and a cotton ball for egg laying.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations